Optimalisasi Pembelajaran Maharatul Qiro`ah di Madrasah Aliyah Uswatun Hasanah Probolinggo : Tantangan dan Solusi dalam Meningkatkan Kualitas Kefasihan Bahasa Arab - Widayanti, Uun; Rofiq Sofa, Ainur (Faidatuna, 2025)
This study aims to identify the challenges in teaching maharatul qiro’ah at Madrasah Aliyah Uswatun Hasanah and propose solutions to enhance students’ fluency in Arabic. As a fundamental language skill, maharatul qiro’ah often encounters various obstacles, including students' limited understanding of Arabic phonology and grammar, low learning motivation, and the lack of diverse teaching methods. To address these issues, this research suggests adopting more varied and interactive teaching approaches, utilizing technology to support reading practice, and improving teachers' competencies through training programs. Additionally, parental and community support is considered a crucial factor in facilitating students’ learning processes. By implementing these strategies, students are expected to improve their reading skills in Arabic texts and gain a more comprehensive mastery of the language, which will contribute to their understanding of Islamic teachings and their application in daily life. The findings of this study are expected to contribute to enhancing the quality of Arabic language instruction at Madrasah Aliyah Uswatun Hasanah and serve as a reference for other educational institutions in developing Arabic learning strategies.